Beyond Approval: What are the Post-Market Surveillance Requirements for AI in Digital Health? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI and Machine Learning ML into digital health has ushered in a new era of diagnostic and therapeutic tools, often...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care